2010
DOI: 10.1103/physrevc.82.014317
|View full text |Cite
|
Sign up to set email alerts
|

Shape phase transition in odd-even nuclei: From spherical to deformedγ-unstable shapes

Abstract: Shape phase transitions in odd-A nuclei are investigated within the framework of the interacting boson-fermion model. The case of a single j = 9/2 fermion coupled to an even-even boson core is considered. This boson core transits from spherical to γ -unstable shapes depending on the value of a control parameter in the boson Hamiltonian. The effect of the coupling of the odd particle to this core along the shape transition and, in particular, at the critical point is discussed. For that purpose, the ground-stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 31 publications
3
36
0
Order By: Relevance
“…This follows because the interaction between the core and the single-particle is expected to be quite strong in the odd-A nuclei when the core is well-deformed. In addition, a detailed comparison of the X(3/ 2j+1) model with the interacting boson-fermion model [42][43][44] and the SD-pair shell model [45,46] for odd-A nuclei would be interesting. Related work is in progress.…”
Section: Discussionmentioning
confidence: 99%
“…This follows because the interaction between the core and the single-particle is expected to be quite strong in the odd-A nuclei when the core is well-deformed. In addition, a detailed comparison of the X(3/ 2j+1) model with the interacting boson-fermion model [42][43][44] and the SD-pair shell model [45,46] for odd-A nuclei would be interesting. Related work is in progress.…”
Section: Discussionmentioning
confidence: 99%
“…One can prove that the spherical to prolate SPTs may occur at η c = (1) is taken into account. Since a single-j shell is considered for the odd fermion, the pure fermion part contributes only an additional constant to the ground state energy [4].…”
Section: Classical Analysis Of the Spherical To Prolate Sptsmentioning
confidence: 99%
“…Shape phase transitions (SPTs) in odd-even nuclei have received some attentions in recent years [1][2][3][4][5][6][7][8][9][10]. Evidences of the spherical to prolate SPT and the associated shape/phase coexistence have been clearly identified in the odd Sm nuclei [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase transitions is also investigate in odd-A nuclei within the framework of interacting boson -fermion model (IBF M ) [8], which describe nuclei in terms of correlated pairs, with L = 0, 2 (s , d bosons), and unpaired particles of angular momentum j (jf ermions).Studies of QP T s in odd-even nuclei were implicitly initiated years ago by Scholten and Blasi [9]. Several explicit studies have recently been made by Alonso et al [10][11][12] and by Boyukata et al [13], who also have suggested a simple form of the IBFM Hamiltonian, particularly well-suited to study QP T s in odd-even nuclei because of their supersymmetric properties. Similar to even-even nuclei, also exists critical point for odd-even and even-odd nuclei but in this case, critical points show with E(5/ j 2j + 1) and X(5/ j 2j + 1) that j is the angular momentum of single nucleon.…”
Section: Introductionmentioning
confidence: 99%